Coagulation and oxidation for controlling ultrafiltration membrane fouling in drinking water treatment: Application of ozone at low dose in submerged membrane tank - Yu,W; Graham,NJD; Fowler,GD (Water Research, 2016)
Coagulation prior to ultrafiltration (UF) is widely applied for treating contaminated surface water sources for potable supply. While beneficial, coagulation alone is unable to control membrane fouling effectively in many cases, and there is continuing interest in the use of additional, complementary methods such as oxidation in the pre-treatment of raw water prior to UF. In this study, the application of ozone at low dose in the membrane tank immediately following coagulation has been evaluated at laboratory-scale employing model raw water. In parallel tests with and without the application of ozone, the impact of applied ozone doses of 0.5 mg L−1 and 1.5 mg L−1 (approximately 0.18 mg L−1 and 0.54 mg L−1 consumed ozone, respectively) on the increase of trans-membrane pressure (TMP) was evaluated and correlated with the quantity and nature of membrane deposits, both as a cake layer and within membrane pores. The results showed that a dose of 0.5 mgO3 L−1 gave a membrane fouling rate that was substantially lower than without ozone addition, while a dose of 1.5 mgO3 L−1 was able to prevent fouling effects significantly (no increase in TMP). Ozone was found to decrease the concentration of bacteria (especially the concentration of bacteria per suspended solid) in the membrane tank, and to alter the nature of dissolved organic matter by increasing the proportion of hydrophilic substances. Ozone decreased the concentration of extracellular polymeric substances (EPS), such as polysaccharides and proteins, in the membrane cake layer; the reduced EPS and bacterial concentrations resulted in a much thinner cake layer, although the suspended solids concentration was much higher in the ozone added membrane tank. Ozone also decreased the accumulation and hydrophobicity of organic matter within the membrane pores, leading to minimal irreversible fouling. Therefore, the application of low-dose ozone within the UF membrane tank is a potentially